Measurement of the energy response of the ATLAS calorimeter to charged pions from $$W^{± }→ τ ^{± }(→ π ^{± }ν _{τ })ν _{τ }$$ W±→τ±(→π±ντ)ντ events in Run 2 data. - Beauchemin, P. H.; Croft, V..; Drobac, A. S.; Kaya, F. I.; Sliwa, K..; Son, H.. (Tufts University. Tisch Library., 2022)
Springer Open.